(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
Learning English in a campus environment is the main focus for improving students’ speaking skills. In this context, this research was conducted to explore the role of native speakers in improving students’ speaking skills in higher education. A descriptive qualitative approach was used, collecting data from research results and previous studies that were still relevant to the research objectives. The results of this research show that constraints, program development strategies, impact evaluation, and implementation of conversation programs with native speakers on campus are crucial aspects of achieving these goals. Therefore, there is a need for management support and availability of resources, program integration in the curriculum, and the use of technology as a strategic step to achieve sustainability and long-term success of conversation programs with native speakers in improving students’ speaking abilities in higher education.